Asas- Asas Pertanggungjawaban Pidana Korporasi - Prakarsa, Ragil Surya; Putri, Naghita Shalsabilla; Putri, Winni Angelia Eka; Rahayu, Rani (PUAN INDONESIA, 2024)
This research aims to analyze the principles underlying corporate criminal responsibility. According to statutory regulations, corporations as legal subjects can be subject to criminal penalties in the same way as humans committing criminal acts. Crimes committed by corporations have wider consequences and more victims, even though sometimes they are not directly victims. Through an in-depth study of various legal and jurisprudential literature, this research identifies and explains key principles such as strict liability, vicarious liability, and identification. In Indonesian laws and regulations, corporations are subjects that can be held accountable before the law. It is hoped that the results of this research can contribute to the development of a more comprehensive understanding of corporate criminal liability in Indonesia.